Platelet-Activating Biominerals Enhanced Injectable Hydrogels With Superior Bioactivity for Bone Regeneration - Chen, Xin; Yan, Jiajun; Jiang, Yingying; Fan, Yunshan; Ying, Zhengran; Tan, Shuo; Zhou, Zhi; Liu, Junjian; Chen, Feng; He, Shisheng (Frontiers in Bioengineering and Biotechnology, 2022)
The refractory bone fracture which is hard to be treated is a common clinical disease. Taking inspiration from the natural process of bone regeneration, we provide a biomimetic strategy to develop a new injectable biomaterial for repairing bone defect, which is mainly composed with platelets, fibrins and biominerals. The biomineral nanoparticles (EACPNs) with amorphous phase are prepared by an enzyme-catalyzed route, and display a platelet-activating property. The composite hydrogel (EPH) of EACPNs, fibrins and platelets is injectable and has similar chemical properties to natural materials in bone regeneration. The dried samples of EPH display a high porous structure which would be favorable for cell attachment and growth. The results from in vitro studies indicate that the EPH has high biocompatibility and superior bioactivity in promoting the osteogenic differentiation of rat bone marrow stem cells (rBMSCs). Furthermore, the results from in vivo studies clearly indicate that the EPH can induce the formation of new collagens and vessels in defect area, and thus leading a faster regeneration of bone defect in 2 weeks. Our study provides a strategy for designing new biomimetic materials, which may be favorable in the treatment of refractory bone fracture.